2021
DOI: 10.3390/cells10113246
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Acquired Genetic Abnormalities on the Clinical Translation of Human Pluripotent Stem Cells

Abstract: Human pluripotent stem cells (hPSC) are known to acquire chromosomal abnormalities, which range from point mutations to large copy number changes, including full chromosome aneuploidy. These aberrations have a wide-ranging influence on the state of cells, in both the undifferentiated and differentiated state. Currently, very little is known on how these abnormalities will impact the clinical translation of hPSC, and particularly their potential to prime cells for oncogenic transformation. A further complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 121 publications
(143 reference statements)
0
18
0
Order By: Relevance
“…As noted above, trisomy 12 is a common aneuploidy in iPSC lines and ESC lines [ 6 , 12 , 21 , 22 , 23 , 37 ]. Conventionally this has been hypothesized to occur through increased expression of growth promoting genes that provide a growth advantage to the variants [ 6 , 14 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted above, trisomy 12 is a common aneuploidy in iPSC lines and ESC lines [ 6 , 12 , 21 , 22 , 23 , 37 ]. Conventionally this has been hypothesized to occur through increased expression of growth promoting genes that provide a growth advantage to the variants [ 6 , 14 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…A variety of genomic abnormalities can affect stem cells in culture. One of the most significant genome changes is aneuploidy [ 19 , 20 , 21 ]. An investigation of over 200 iPSC lines found that 12.5% of the cultures examined had an abnormal karyotype, while a study of 125 ESC lines found that 34% of cell lines contained abnormal karyotypes; both studies demonstrate the widespread occurrence of chromosomal aberrations [ 12 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, the risk of tumorigenicity of iPSCs is a significant concern [5] , [6] , which mainly result from three factors including undifferentiated and/or immature cells in the final cell products that differentiate from the iPSCs, tumorigenic property of reprogramming factors in the iPSCs, and genetic mutations of iPSCs during in vitro culture [7] . Even very small amount of residual iPSCs or lineage-specific stem cells in the transplant could result in formation of teratoma or other tumors.…”
Section: The Challenge Of Tumorigenicity In Induced Pluripotent Stem ...mentioning
confidence: 99%
“…At a research level, these cells can be a valuable tool to gain insight into the mechanisms underlying human organogenesis and enhance understanding of disease mechanisms. Moreover, they can serve as an alternative in vitro platform for drug and toxicology testing to bypass the need for animal models and thus avoiding issues related to failed translation to humans as well as the ethical concerns surrounding animal research [8], hPSC-based therapies for the treatment of degenerative diseases including heart disease, diabetes or neurodegenerative disease have been developed by the differentiation of hPSCs to the affected cell type for subsequent transplantation into patients. In fact, clinical trials for regenerative medicine using derivatives of these cells are already underway or are planned and have, up to now, shown the cells to be generally safe [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%